Kesesuaian Lama Perawatan dengan Standar Clinical Pathway pada Kasus Hematologi dengan Tindakan Kemoterapi Pasien BPJS Non PBI di RSUP Dr. Kariadi Kota Semarang - Dwi Ratna Yuliyanti; Kriswiharsi Kun Saptorini (Dian Nuswantoro Semarang, 2016)
The indicators for assessing the efficiency of inpatient health care is Length Of Stay (LOS). This study analyzed appropriateness the length of stay (LOS) and clinical pathway standar of non PBI-BPJS patient cases of hematology with chemotherapy in 2015. This was descriptive study,Â data collected by observation. The research object were medical record documents and casemix data.Based on results study, the most of age was 0-10 years old (36%), female (61%), main diagnosis was acute lymphoblastic leukemia (ALL) (80%), without secondary diagnosis (53,2%),Â in third severity level (87%), and length of stay was 0 -10 days (47%). The length of stay that appropriate with the standard in hospital (60%) was higher than length of stay that inappropriate of clinical pathway standard (40%).The percentage of the value of claim losses reached 57,8% and the remaining 42,2% was an advantage. The percentage of the losses, were mostly occured on appropriate clinical pathways length of stay (85%) than inappropriate clinical pathways length of stay (16%), despite the losses occured, the advantages that obtained were more than the disadvantages.Therefore, clinical pathways need to be implemented properly in order to avoid the loss in the value of the BPJS claim.Keyword : length of stay, clinical pathways, BPJS claim, hematology